1990
DOI: 10.1128/jvi.64.11.5295-5300.1990
|View full text |Cite
|
Sign up to set email alerts
|

Concatameric replication of Epstein-Barr virus: structure of the termini in virus-producer and newly transformed cell lines

Abstract: The linear form of Epstein-Barr virus (EBV) DNA has homologous direct tandem repeats of approximately 500 bp at each terminus (TR). After infection, EBV DNA circularizes via the TR to form the intracellular episomal DNA. To analyze the mechanism of the synthesis of linear DNA through possible replicative intermediates, the terminal fragments were identified in the total intracellular DNA and the covalently closed circular DNA from a productively infected cell line after induction of replication or after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The EBV terminal repeat unit varies between approximately 500 and 1,000 nucleotides in length [Gilligan et al, 1990], and variation in the number of EBV terminal repeat units arises during productive EBV replication as a consequence of variable-site cleavage of the concatemeric viral genome during virion packaging [Sato et al, 1990;Zimmermann and Hammerschmidt, 1995]. After infection of an individual, a single EBV genotype may generate numerous EBV termini variants that infect multiple different B-lymphocytes within that individual.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV terminal repeat unit varies between approximately 500 and 1,000 nucleotides in length [Gilligan et al, 1990], and variation in the number of EBV terminal repeat units arises during productive EBV replication as a consequence of variable-site cleavage of the concatemeric viral genome during virion packaging [Sato et al, 1990;Zimmermann and Hammerschmidt, 1995]. After infection of an individual, a single EBV genotype may generate numerous EBV termini variants that infect multiple different B-lymphocytes within that individual.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of Southern blot analyses suggested that TRBV7 + and TRBV9 + T cell populations were infected with the same strain of EBV that had the same number of terminal repeats, it has been reported that two different EBV strains can have the same numbers of terminal repeats [21]. For this reason, Total RNA was extracted from total PBMNC, TRBV7 + cells and TRBV9 + cells and subjected to RT.…”
Section: Infection Of the Two Kinds Of T Cell Clones With The Same Momentioning
confidence: 99%
“…Lytic replication differs from the latent amplification state in that multiple rounds of replication are initiated within ori-Lyt, and the replication process has a greater dependence on EBV-encoded proteins. Moreover, lytic DNA replication results in the generation of high-molecular-weight concatemeric molecules which are subsequently cleaved into unit-length genomes and packaged into virions (16,59,73). The lytic replication cycle, which occurs in the oropharynx (65), can be induced in latently infected B cells by treatment with phorbol esters, by crosslinking of surface immunoglobulin, or by introduction of the EBV BZLF1-encoded transactivator, Zta (13,66,74).…”
mentioning
confidence: 99%